PENINGKATAN PERTUMBUHAN, SERAPAN UNSUR HARA N, P, K SERTA PRODUKSI TANAMAN JAGUNG DI ENTISOL KALIDAWIR, TULUNGAGUNG AKIBAT APLIKASI PUPUK KANDANG SAPI DAN PUPUK NPK - Al Azizu Saifulloh; Retno Suntari (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2022)
Entisols are newly formed soil types and are commonly found in Indonesia, with a distribution of Â±3 million ha distribution. Entisol Kalidawir has a slightly acidic pH value of 5.8 and contains very low total-nitrogen (N) and available-phosphorus (P) nutrients, calcium (Ca), sodium (Na) and magnesium (Mg) in the exchangeable base are also low and clay loam texture. Low soil nutrients and organic matter can have an impact on plant growth and production Maize is one of the most widely cultivated food crops in Indonesia. The purpose of this study was to analyze various doses of the combination of cow manure and NPK fertilizer on N, P and potassium (K) uptake, growth and production of maize. The results showed that the application of 20 t ha-1 of cow manure and 400 kg ha-1 of NPK fertilizer at observations 27 and 54 days after planting increased growth in height and number of leaves of corn plants and increased nutrient uptake of N, P, and K, respectively. Also reached 1, 0.14, and 0.82 g plant-1 and 5.52, 0.83, and 5.11 g plant-1. In addition, it produces the highest corn production of 10.53 t ha-1.